Pengaruh Variasi Drill Dropshot terhadapPeningkatan Ketepatan Dropshot pada Siswa SMAN 4 Sungai Penuh - Yantonius Baene; Jonika Trishandra; Cundra Bahar (Journal on Education, 2024)
Based on the background of the problem, the accuracy of dropshot shots of SMAN 4 Sungai Penuh students is still low. Based on the results of observations when doing training or conducting matches, SMAN 4 Sungai Penuh students are very lacking in performing badminton dropshot skills, and there are often mistakes in making a movement that should be able to reach the ball easily and returned to the opponent, but the results cannot be returned at all. Therefore, to find out the above problems, the authors conducted drilling exercises to increase dropshot on students of SMAN 4 Sungai Penuh to improve the ability of dropshot shots to be better. This study aims to determine the effect of dropshot drill variation on improving dropshot accuracy in students of SMAN 4 Sungai Penuh. The research conducted is an experimental study conducted with the aim of knowing whether or not there is an effect of something that is imposed on the sample to be studied. This research was conducted at the Juanda Sport badminton court and PBSI Hall Sungai Penuh City with 12 athletes with details of the initial test, namely the test before doing the drill training method and the final test, namely the test after doing the drill training method. Based on data analysis, the research has been proven by the results of a normal normality test, a homogeneous homogeneity test and a T test with Thitung 10.10 whose results are significant with a comparison of Ttabel 2.22 this means that the research hypothesis is accepted at the 95% confidence level. So it can be concluded that drilling practice can improve the accuracy of dropshot on students of SMAN 4 Sungai Penuh. So the researcher suggests that sports trainers and teachers provide variations of racket dropshot drill exercises to improve dropshot accuracy in badminton activities.